Identifying and addressing disparities in the evaluation and treatment of children with growth hormone deficiency - Beliard, Kara; Wu, Vickie; Samuels, Julie; Lipman, Terri H.; Rapaport, Robert (Frontiers in Endocrinology, 2022)
Health disparities are a significant cause of concern globally and in the United States. Disparities have been additionally highlighted throughout the ongoing COVID-19 pandemic during which populations of color have been the most affected by the disease. Social determinants of health, race, ethnicity, and gender have all contributed to disparate outcomes and disparities spanning all age groups. Multiple socio-ecological factors contribute to disparities and different strategies have been proposed. The purpose of this paper is to provide an overview of disparities in pediatric treatment and outcomes, with a focus on children with endocrine disorders.